1995
DOI: 10.1007/bf00008569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heterotrophic bacterial production rates in early spring in the turbid estuaries of the Scheldt and the Elbe

Abstract: In spring bacterial production rates were estimated by tritiated thymidine incorporation in the turbid estuaries of the rivers Scheldt and Elbe . Bacterial production rates in the Scheldt were 5 times higher than in the Elbe . In the Scheldt bacterial production rates correlated better with the DOC concentration than in the Elbe . Organic matter concentrations in the marine part of the estuaries were the same while in the brackish part concentrations in the Scheldt were much more higher. In the Scheldt, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Due to a reduction of light availability in the port, and an increase of suspended particulate matter, primary production is inhibited in this region (Goosen et al, 1995;Wolfstein and Kies, 1999), and the fresh phytoplankton biomass brought in by the Elbe water is an optimal source for remineralization by heterotrophic bacteria (Kerner, 2000). Enhanced remineralization and decreasing phytoplankton activity leads to increased O 2 consumption and a decrease of O 2 production, respectively, leading to the observed minimal O 2 concentrations in the deep Hamburg port region (Schöl et al, 2014).…”
Section: Discussion N 2 O Source Regions In the Estuarymentioning
confidence: 99%
“…Due to a reduction of light availability in the port, and an increase of suspended particulate matter, primary production is inhibited in this region (Goosen et al, 1995;Wolfstein and Kies, 1999), and the fresh phytoplankton biomass brought in by the Elbe water is an optimal source for remineralization by heterotrophic bacteria (Kerner, 2000). Enhanced remineralization and decreasing phytoplankton activity leads to increased O 2 consumption and a decrease of O 2 production, respectively, leading to the observed minimal O 2 concentrations in the deep Hamburg port region (Schöl et al, 2014).…”
Section: Discussion N 2 O Source Regions In the Estuarymentioning
confidence: 99%
“…(3) and (4), Y decreases toward a minimum value. In the model, freshwater phytoplankton and bacterioplankton in the river are subject to salt stress when freshwater mixes with saltwater; and the freshwater microbial populations die in this zone (Flameling and Kromkamp, 1994;Goosen et al, 1995). In the model, the salinity also limits the seaward distribution of saline water plankton, invertebrates (e.g.…”
Section: Article In Pressmentioning
confidence: 99%
“…showed a highly significant (p < 0.0001, r2 = 0.56 to 0.74) correlation in the lower estuary, Stns l to 5. Goosen et al (1995) showed in the Schelde estuary that Bacterial growth rates bacterial production changed substantially during a tidal cycle and thus as a function of changing salinity.…”
Section: Salinity (Psu)mentioning
confidence: 99%
“…Billen et al (1988) predicted intensive bacterial growth, by modelling microbial processes, and Soetaert & Herman (1995b) showed a very high degree of heterotrophy in the Schelde estuary. By in situ measurements Goosen et al (1995) showed that in spring, bacteria! production rates in the S c h e l d~ P S~I Iary are among the highest reported for temperate estuaries.…”
Section: Introductionmentioning
confidence: 99%